Behavioral analysis on IPv4 malware in both IPv4 and IPv6 network environment - M., Zulkiflee; Mohd Faizal Abdollah, Faizal M.A.; IOM, Fairuz; Abu, Nur Azman; Sahib@Sahibuddin, Shahrin (2011)
Malware is become an epidemic in computer network nowadays. Malware attacks are a significant threat to networks. A conducted survey shows malware attacks may result a huge financial impact. This scenario has become worse when users are migrating to a new envi-ronment which is Internet Protocol Version 6. In this paper, a real Nimda worm was released on to further understand the worm behavior in real network traffic. A controlled environment of both IPv4 and IPv6 network were deployed as a testbed for this study. The result be-tween these two scenarios will be analyzed and discussed further in term of the worm behavior. The experiment result shows that even IPv4 malware still can infect the IPv6 network environment without any modification. New detection techniques need to be proposed to remedy this problem swiftly.